Fe(III) Reduction and U(VI) Immobilization by Paenibacillus sp. Strain 300A, Isolated from Hanford 300A Subsurface Sediments - Ahmed, Bulbul (American Society for Microbiology, 2012)
A facultative iron-reducing [Fe(III)-reducing] Paenibacillus sp. strain was isolated from Hanford 300A subsurface sediment biofilms that was capable of reducing soluble Fe(III) complexes [Fe(III)-nitrilotriacetic acid and Fe(III)-citrate] but unable to reduce poorly crystalline ferrihydrite (Fh). However, Paenibacillus sp. 300A was capable of reducing Fh in the presence of low concentrations (2 μM) of either of the electron transfer mediators (ETMs) flavin mononucleotide (FMN) or anthraquinone-2,6-disulfonate (AQDS). Maximum initial Fh reduction rates were observed at catalytic concentrations (<10 μM) of either FMN or AQDS. Higher FMN concentrations inhibited Fh reduction, while increased AQDS concentrations did not. We also found that Paenibacillus sp. 300A could reduce Fh in the presence of natural ETMs from Hanford 300A subsurface sediments. In the absence of ETMs, Paenibacillus sp. 300A was capable of immobilizing U(VI) through both reduction and adsorption. The relative contributions of adsorption and microbial reduction to U(VI) removal from the aqueous phase were ∼7:3 in PIPES [piperazine-N,N′-bis(2-ethanesulfonic acid)] and ∼1:4 in bicarbonate buffer. Our study demonstrated that Paenibacillus sp. 300A catalyzes Fe(III) reduction and U(VI) immobilization and that these reactions benefit from externally added or naturally existing ETMs in 300A subsurface sediments.